THE EFFECT OF MOTIVATION ON ENGLISH LITERATURE READING TO MEDICAL STUDENTS’ BLOCK EXAMINATION SCORE - Dinda Carissa; Yunia Hastami; Eti Poncorini Pamungkasari (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2020)
Background: The reading interest rate of Indonesian society is relatively low (approximately 0,001). Meanwhile, during their study, medical students have to read numerous English literatures. Previous research showed that reading activity can be improved by reading motivation. However, studies about Indonesian medical students reading motivation on English literature are still limited. This study aims to assess the effect of students’ English literature reading motivation to the block exam average score.Methods: This was a cross-sectional study conducted in January 2018. We used stratified random sampling, and we found 274 samples that fit with inclusion and exclusion criterias selected. The motivation was assessed using the English literature reading motivation scale, block exam test results were obtained through the academic database. Data were analyzed with multiple linier regression test.Result: Students’ English reading motivation increased the block exam average score of Medical Students. Every increase of one score of motivation significantly increase 0,10 score block exam average (p<0,001). Furthermore, every increase of one year of study can significantly increase 3,53 of block exam average score (p<0,001); R2=18,3 %. English literature reading motivation of medical students UNS is in middle category.Conclusion: English literature reading motivation increase the block exam average score of Medical Students in UNS.